2018
DOI: 10.1080/17450101.2018.1466504
|View full text |Cite
|
Sign up to set email alerts
|

Constructing a city, building a life: Brazilian construction workers’ continuous mobility as a permanent life strategy

Abstract: This article provides an ethnographic analysis of domestic labor mobility among Brazilian construction workers in the context of the 2016 Summer Olympics in Rio de Janeiro. We start from the premise that mobile laborers are crucial for the physical development and expansion of cities. However, the importance of domestic migrants in this process is insufficiently addressed in mobility studies. Building on existing research on domestic population movements in Brazil, we argue that the current generation of mobil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 41 publications
0
10
0
Order By: Relevance
“…With short deadlines, they work irregular and long hours and during hot seasons, and they live in substandard and crowded housing, as documented in construction projects in the Olympics in Beijing and the planned FIFA World Cup in Qatar 1516. Ethnographic, language, and psychosocial challenges also affect the health and social conditions of migrant construction workers concerned in big sporting events 171819…”
Section: Labour Migrants’ Healthmentioning
confidence: 99%
“…With short deadlines, they work irregular and long hours and during hot seasons, and they live in substandard and crowded housing, as documented in construction projects in the Olympics in Beijing and the planned FIFA World Cup in Qatar 1516. Ethnographic, language, and psychosocial challenges also affect the health and social conditions of migrant construction workers concerned in big sporting events 171819…”
Section: Labour Migrants’ Healthmentioning
confidence: 99%
“…Ethnographic studies have shown that the inability of labour migrants to adequately speak or understand the working language or languages of their managers increases their vulnerability 513. Their temporary stay in the host country and their often unrecognised contribution to the big sporting event undermine their wellbeing, creating an overwhelming sense of disillusionment and disappointment 78.…”
Section: Evidence On Health Needsmentioning
confidence: 99%
“…For example, research is needed on healthcare services available to migrant workers before leaving their home country, in the host country, and on their return home, including access to screening, preventive healthcare, and vaccination. This information is needed to better understand the factors that impede or facilitate migrant workers’ access to public or private health systems for acute needs during their stay in the host country and the obligations of governments and private companies that manage their stay 5633. Much attention has been given recently to the extent to which migrant populations in high income countries will have access to covid-19 vaccines, with the World Health Organization highlighting low skilled labour migrants as a priority group 3435.…”
Section: Strengthening the Evidence To Improve Healthmentioning
confidence: 99%
See 2 more Smart Citations